Circulating MicroRNA-21 is Downregulated in Patients with Metabolic Syndrome - HE, Qing Fang; WANG, Li Xin; ZHONG, Jie Ming; HU, Ru Ying; FANG, Le; WANG, Hao; GONG, Wei Wei; ZHANG, Jie; PAN, Jing; YU, Min (Biomedical and environmental sciences, 2016)
The microRNA-21 （miR-21） is known to play a major role in cancer progression; however, its function in the cardiovascular system appears to be even more complex and conflicting. To characterize miR-21 expression in the plasma of individuals with or without metabolic syndrome （MetS）, 58 MetS cases and 96 non-MetS controls were investigated.